Antineoplastic effects of clove buds (Syzygium aromaticum L.) in the model of breast carcinoma. Issue 11 (19th May 2017) - Kubatka, Peter; Uramova, Sona; Kello, Martin; Kajo, Karol; Kruzliak, Peter; Mojzis, Jan; Vybohova, Desanka; Adamkov, Marian; Jasek, Karina; Lasabova, Zora; Zubor, Pavol; Fialova, Silvia; et al.
Abstract: It is supposed that plant functional foods, rich in phytochemicals, may potentially have preventive effects in carcinogenesis. In this study, the anticancer effects of cloves in the in vivo and in vitro mammary carcinoma model were assessed. Dried flower buds of cloves (CLOs) were used at two concentrations of 0.1% and 1% through diet during 13 weeks after the application of chemocarcinogen. After autopsy, histopathological and immunohistochemical analyses of rat mammary carcinomas were performed. Moreover, in vitro evaluation using MCF‐7 cells was carried out. Dietary administered CLO caused the dose‐dependent decrease in tumour frequency by 47.5% and 58.5% when compared to control. Analysis of carcinoma cells in animals showed bcl‐2, Ki67, VEGFA, CD24 and CD44 expression decrease and Bax, caspase‐3 and ALDH1 expression increase after high‐dose CLO administration. MDA levels were substantially decreased in rat carcinomas in both CLO groups. The evaluation of histone modifications revealed increase in lysine trimethylations and acetylations (H4K20me3, H4K16ac) in carcinomas after CLO administration. TIMP3 promoter methylation levels of CpG3, CpG4, CpG5 islands were altered in treated cancer cells. An increase in total RASSF1A promoter methylation (three CpG sites) in CLO 1 group was found. In vitro studies showed antiproliferative and pro‐apoptotic effects of CLO extract in MCF‐7 cells (analyses of cytotoxicity, Brdu, cell cycle, annexin V/PI, caspase‐7, Bcl‐2 and mitochondrial membrane potential). This study showed a significant anticancer effect of clove buds in the mammary carcinoma model in vivo and in vitro .